Tethered Space Robot : Dynamics, Measurement, and Control - Huang, Panfeng; Meng, Zhongjie; Guo, Jian; Zhang, Fan (Academic Press, 2017)
Tethered Space Robot: Dynamics, Measurement, and Control discusses a novel tethered space robot (TSR) system that contains the space platform, flexible tether and gripper. TSR can capture and remove non-cooperative targets such as space debris. It is the first time the concept has been described in a book, which describes the system and mission design of TSR and then introduces the latest research on pose measurement, dynamics and control. The book covers the TSR system, from principle to applications, including a complete implementing scheme. A useful reference for researchers, engineers and students interested in space robots, OOS and debris removal.